The radicalism of departure : a reassessment of Max Stirner's Hegelianism - Spiessens, Jeff (Cambridge Scholars Publishing, 2018)
To date, the philosophy of Max Stirner (1806-1856) has not attracted much academic attention. An early critic of Karl Marx and precursor of existentialist thought, he is nevertheless remembered as a radical Young Hegelian engaged in an unsuccessful attempt to move 'beyond Hegel'. Arguing that this image of Stirner is based on a faulty interpretation of his relationship to Hegelian philosophy, this book proposes an entirely new reading of his philosophical magnum opus Der Einzige und sein Eigentum. In this work, traditional philosophy, epitomized by Hegel, is reduced to the property of the uniq.